Direct Distribution Regulation by Foreign Direct Investment in the Trade Sector: A Comparative Study Between Indonesia and Singapore - Shane Evelina; Gunardi Lie (Lambung Mangkurat Law Journal, 2025)
This research aims to analyze and compare the regulations governing foreign direct investment in direct distribution activities within the trade business sector, specifically between Indonesia and Singapore. The phenomenon of direct distribution by foreign investors poses challenges for domestic businesses, particularly micro, small, and medium enterprises, as it has the potential to create competitive disparities. In Indonesia, direct distribution activities by foreign direct investment are subject to the provisions of Law Number 25 of 2007 on Investment, which has undergone partial amendments through several subsequent regulations. However, the implementation of these regulations has not fully reflected protection for domestic businesses. Meanwhile, Singapore adopts a more liberal approach to foreign direct investment but maintains oversight mechanisms through specific authorities and administrative requirements for foreign companies. This study seeks to address one key issue: what are the fundamental differences in the regulatory approaches of Indonesia and Singapore toward direct distribution by foreign direct investment? The research employs a normative or doctrinal method with a comparative approach. Secondary data were obtained from applicable laws and regulations, legal literature, and institutional policies in both countries. The findings indicate that Singapore emphasizes ease of market access for foreign direct investment with minimal sectoral restrictions, whereas Indonesia operates within a framework of selective protectionism that lacks consistency. Therefore, there is a need for reconstructing foreign direct investment regulations in Indonesia that are not only pro-investment but also promote economic justice and sustainable national development.